One health : transformative enterprises, wellbeing and education in the knowledge economy - Formica, Piero (Emerald Publishing, 2023)
Bringing together a diverse collection of authors to examine the concept of One Health - the interlinking of the economy and the health of humans, other living beings, and nature - Piero Formica investigates how transformative enterprises and advanced technologies can improve the health of the planet and its people.